2001
DOI: 10.1103/physrevlett.88.015701
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Pinned Modulation Wave in Incommensurate bis (4-chlorophenyl) sulfone (BCPS)

Abstract: We show that both the anomalously huge resonance-frequency dependence of the (35)Cl nuclear quadrupole resonance (NQR) spin-lattice relaxation time in BCPS, reported here for the first time, and its anomalous temperature dependence can be explained by large-scale fluctuations of the pinned modulation wave instead of small-scale fluctuations (phasons and amplitudons). The results were obtained by measuring the laboratory (T(1Q)) and rotating frame (T(1Q,rho)) (35)Cl relaxation times. This is the first time that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2002
2002
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
0
11
1
Order By: Relevance
“…The further decrease of 35 Cl NQR spinlattice relaxation time in the IC phase 20,21 does not appear in our high-field measurements. Hence, it is a frequencydependent effect in relation with the NQR relaxation rate measurements in zero field and in the presence of weak rf fields 21 and in 35 Cl NMR measurements at lower Larmor frequencies but not a contradiction to the predominance of phason and amplitudon fluctuations below T i .…”
Section: B Spin-lattice Relaxation Measurementscontrasting
confidence: 71%
See 3 more Smart Citations
“…The further decrease of 35 Cl NQR spinlattice relaxation time in the IC phase 20,21 does not appear in our high-field measurements. Hence, it is a frequencydependent effect in relation with the NQR relaxation rate measurements in zero field and in the presence of weak rf fields 21 and in 35 Cl NMR measurements at lower Larmor frequencies but not a contradiction to the predominance of phason and amplitudon fluctuations below T i .…”
Section: B Spin-lattice Relaxation Measurementscontrasting
confidence: 71%
“…20, this curious behavior of the relaxation time below T i cannot be understood within the standard theory of the spin relaxation of the incommensurate systems. Subsequently these results were confirmed by Blinc et al 21 and in an attempt to explain this incongruous behavior, they suggested that the spin-lattice relaxation is induced by a dominating influence of "large scale" fluctuations ͑␦ 2 ӷ 1͒ of the modulation wave, contrary to the small phase ͑␦ 2 Ӷ 1͒ and amplitude ͑␦〈 2 Ӷ 1͒ fluctuations usually assumed. This situation shows that several points in the previous 35 Cl NQR studies need further consideration and suggest to perform 35 Cl NMR measurements on BCPS.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…1) exhibits a phase transition from a normal phase to an incommensurate (IC) modulated phase occurring at 150 K [1]. This observation has created a new interest in this compound , which has since then been extensively studied by X-ray diffraction [2,3], neutron scattering [4], NMR [5], NQR and Raman spectroscopy [6,7]. Elastic neutron measurements, Cl NQR and calorimetric measurements have indicated that the incommensurate phase is stable down to very low temperature (4.5 K) with the presence of high-order satellite reflections and intensities increasing on cooling [8,9].…”
Section: Introductionmentioning
confidence: 99%